Factors associated with daily life physical activity in patients with asthma. Issue 10 (15th August 2018) - Hennegrave, Florence; Le Rouzic, Olivier; Fry, Stéphanie; Behal, Hélène; Chenivesse, Cécile; Wallaert, Benoit
Abstract: Background and Objectives: Little is known about the consequences of asthma on daily life physical activity (DLPA ). The aim of this study was to evaluate DLPA and determine its relationship to clinical and functional parameters in patients with asthma. Methods: This was a single‐center prospective study of DLPA conducted between May 2015 and June 2016 in northern France. Fifty‐one adult patients with asthma and 36 healthy control subjects were enrolled. Four DLPA parameters were assessed for 5 consecutive days with a physical activity monitor: number of steps walked per day (SPD), total energy expenditure (EE, in kcal/day), EE spent in physical activity requiring ≥3 metabolic equivalents (METs), and time (min) spent in activities requiring ≥3 METs. Clinical characteristics, pulmonary function tests, 6‐minute walk test, and four questionnaires (modified Medical Research Council [mMRC] for dyspnea, asthma control test [ACT], quality of life [AQLQ], and hospital anxiety and depression scale [HADS]), were evaluated. Comparisons of DLPA parameters between the two groups were performed using an analysis of covariance adjusted for age, sex, and body mass index (BMI). Relationships between DLPA parameters and patient characteristics were assessed in multivariable linear regression models. Results: Compared with patients with mild/moderate asthma, those with severe asthma had lower mean (± standard deviation) forced expiratory volume in 1 s (FEV1 ) (66 ± 24 vs 94 ± 15% predicted, P < 0.001), ACT score (16.7 ± 4.5 vs 19.8 ± 4.2, P = 0.015), and AQLQ score (157 ± 40 vs 184 ± 33, P = 0.012). There were no significant differences between the two groups in SPD (6560 ± 3915 vs 8546 ± 3431; adjusted P = 0.95), EE in physical activity requiring ≥3 METs (620 ± 360 vs 660 ± 140 kcal/day; P = 0.86), time spent in activities requiring EE ≥3 (120 ± 54 vs 121 ± 32 min/day; P = 0.69), or total EE (2606 ± 570 vs 2666 ± 551 kcal/day; P = 0.80). These four DLPA measures showed strong inter‐parameter correlations in patients with asthma ( r = 0.37–0.95, all P < 0.01). All four parameters were lower in the patients with asthma group than in the control group: SPD, 7651 ± 3755 vs 11704 ± 4054 (adjusted P < 0.001); EE in activities requiring ≥3 METs, 642 ± 360 vs 852 ± 374 kcal/day (adjusted P = 0.041); time spent in activities requiring ≥3 EE, 120 ± 73 vs 189 ± 85 min (adjusted P = 0.005); and total EE, 2639 ± 555 vs 2746 ± 449 kcal/day (adjusted P = 0.007). In the patients with asthma group, the number of SPD correlated with age, FEV1, mMRC score, 6‐minute walk test distance, and HADS scores, but not with BMI or ACT test score. Using multivariate analysis, the number of SPD was associated with only age, anxiety, and FEV1, whereas total EE was associated with mMRC score and BMI. Conclusion: Age, anxiety, and FEV1 were significantly associated with the number of SPD in patients with asthma. Addressing anxiety should be further studied as way to attempt to increase physical activity in patients with asthma.